ESTIMATION OF STATURE FROM NASAL HEIGHT IN MALE AND FEMALE STUDENTS IN UDAIPUR - ACHARYA, SUNITA; SHRIVASTAVA, BHAVANA; BHARAMBE, VAISHALY KISHORE; MEDATWAL, BHUPESH (International Journal of Current Pharmaceutical Research, 2024)
Objective: Stature refers to a person's height when standing upright. It is a vital measure of physical identity. In archaeological operations or forensic exams following a mass disaster, height is estimated using rudiments or bone pieces for identification. In order to determine stature, separate regression formulae should be developed for each population group. Methods: This cross-sectional study was conducted at Department of Anatomy, Pacific Institute of Medical Sciences, Umarda, and Udaipur. A total of 110 students (55 males and 55 females) aged between 18 to 25 y, participated in this study. Those with craniofacial defects were excluded from study. Height was measured from vertex to floor by stadiometer. Results: The study showed that in males mean values are significantly higher than females for both nasal height as well as stature; nasal height in (males 48.54±3.584 mm; females 46.75±3.763 mm) and stature in (male 170.3±7.902 cm; female 159.61±5.383 cm). In total student’s as well as in males and females, nasal height had a weak positive linear relationship with stature; r=0.283 in total students, r=0.222 for male and r=0.123 for female. The regression equation for stature and nasal height was found to be Y=134.053+0.648× nasal height for total students, Y=146.487+0.491×nasal height for males, Y=151.328+0.177× nasal height for females. Conclusion: The observed correlation is statistically significant in total students (p value<0.05) but not significant in males and females (p value>0.05). Overall nasal height had a weak positive linear correlation with stature.